معايير النص عند روبرت دي بوجراند وأثرها في فهم الخطاب النبوي: حديث دواء المبطون نموذجا = Robert De Beaugrande’s textual standards and its impact on understanding of prophetic discourse: hadith of the treatment for upset stomach as example - Abd Ghani, Muhammad Izwan; Ali, Asem Shehadeh Saleh (USIM Press, 2022)
ّ تناولت هذه الدراسة التحليل لبنية نص بمعطيات اللسانيات الحديثة في تتمثل معايير النص التي اقترحها روبريت دي بوجراند؛ بحيث إنها من أهم الوسائل اللغوية التي تقوم بدورها في تشريح بناء النص، وتحقيق تماسكه النصي وترابطه المفهومي والتواصلي. تهدف الدراسة إلى الكشف عن عناصر النص، وهي: الاتساق، والانسجام، والقصدية، والمقبولية، والموقفية، والإعلامية والتناص، وبيان أثرها في فهم الخطاب النبوي. والمنهج المتبع لهذه الدراسة هو المدخل الكيفي والاعتماد على منهج تحليل المحتوى؛ إذ يتطرق هذا المنهج إلى وصف وتحليل وشرح نص الحديث في ضوء علم اللغة النصي. وتشير النتائج إلى أن الحديث الذي يتحدث عن دواء المبطون تتوافر فيه عناصر معايير النص السبعة؛ ً ابتداء من معيار الاتساق التي تتوافر عناصره؛ من الإحالة، والاستبدال، والحذف، والوصل والتكرار، ويظهر فيه معيار الانسجام وعناصره من المقام، والسياق، والمجاز والقرائن، وتتبين مظاهر القصدية والمقبولية في الحديث، كما تكشف كذلك معايير الموقفية، والإعلامية والتناص فيه، ما تؤكد هذه المعايير على تماسك وترابط الحديث المفهومي والتواصلي الكلمات المفتاحية : علم اللغة النصي، معايير النص، روبرت دي بوجراند، الطب النبوي، دواء المبطون ً = This study analysed the text structure with textual standards proposed by Robert de beaugrande where they are among the essential tools of language that play a role in dissecting the construction of the text, achieving its textual coherence, conceptual interdependence, and communication. The study aims to uncover its elements: cohesion, coherence, intentionality, acceptability, situationally, informativity, and intertextuality and their impact on the understanding of prophetic discourse. The approach for this study is qualitative and based on the content analysis approach. This approach addresses the description, analysis, and explanation of the hadith in the light of text linguistics. The results indicate that this hadith has the seven elements of the textual standards, starting with the cohesion whose elements are available; reference, substitution, ellipsis, conjunction, and recurrence, and the criterion of coherence and its elements are the situation, context, metaphor and correlation, and the manifestations of intentionality and acceptability in the hadith are revealed, as well as the criteria of situationally, informativity and intertextuality in it, which all emphasise the coherence, conceptual interdependence, and communication of the hadith and their impact on the interpretation and understanding of the hadith in the recipient. Keywords: Text linguistics, textual standards, textual measures, Robert De Beaugrande, Prophetic medicine, treatment for upset stomach.